2022
DOI: 10.1038/s41467-022-28809-4
|View full text |Cite
|
Sign up to set email alerts
|

The arginine methyltransferase PRMT7 promotes extravasation of monocytes resulting in tissue injury in COPD

Abstract: Extravasation of monocytes into tissue and to the site of injury is a fundamental immunological process, which requires rapid responses via post translational modifications (PTM) of proteins. Protein arginine methyltransferase 7 (PRMT7) is an epigenetic factor that has the capacity to mono-methylate histones on arginine residues. Here we show that in chronic obstructive pulmonary disease (COPD) patients, PRMT7 expression is elevated in the lung tissue and localized to the macrophages. In mouse models of COPD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 97 publications
(115 reference statements)
2
36
0
Order By: Relevance
“…Under the stimulation of CS, macrophages, neutrophils, and lymphocytes are recruited in the small airways and the lung parenchyma to secret inflammatory factors to induce oxidative stress and pulmonary epithelial cells death [ 84 , 85 ]. Among them, the accumulation of monocyte-derived macrophages increases leukotriene B4 (LTB4) secretion and triggers the expression of ACSL4 on epithelial cells, thereby inducing alveolar epithelial type 2 (AT2) cell ferroptosis [ 85 ]. In addition, COPD patients are companied with iron homeostasis imbalance and lipid peroxidation.…”
Section: The Role Of Ferroptosis In Pulmonary Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the stimulation of CS, macrophages, neutrophils, and lymphocytes are recruited in the small airways and the lung parenchyma to secret inflammatory factors to induce oxidative stress and pulmonary epithelial cells death [ 84 , 85 ]. Among them, the accumulation of monocyte-derived macrophages increases leukotriene B4 (LTB4) secretion and triggers the expression of ACSL4 on epithelial cells, thereby inducing alveolar epithelial type 2 (AT2) cell ferroptosis [ 85 ]. In addition, COPD patients are companied with iron homeostasis imbalance and lipid peroxidation.…”
Section: The Role Of Ferroptosis In Pulmonary Diseasesmentioning
confidence: 99%
“…In addition, COPD patients are companied with iron homeostasis imbalance and lipid peroxidation. Under CS exposure, the NOCA4-mediated ferritinophagy pathway and IRP2 upregulated mitochondrial iron overload are initiated, whereas GPX4 related defending pathway is inhibited [ 85 87 ].…”
Section: The Role Of Ferroptosis In Pulmonary Diseasesmentioning
confidence: 99%
“…The first kinds of macrophages differentiate themselves during the inflammatory affections. In fact, the abnormal amount of chemokines produced during this pathological alteration, such as IFN-γ, the macrophage colony-stimulating factor (M-CSF), CCL2, CCL5, etc., induced a strong chemo-attraction of circulating monocytes, and after extravasation, they differentiated into macrophages [ 58 , 59 ]. On the other hand, tissue-resident macrophages exist in quite all tissues, e.g., in the liver (Kupffer cells), lung (alveolar macrophages), kidneys (mesangial cells), brain (microglial cells), etc., and contribute actively to the maintenance of homeostasis conditions [ 60 ].…”
Section: Role Of Tumor Microenvironment In Cancer Progressionmentioning
confidence: 99%
“…Dihydroquercetin treatment protected against COPD by inhibiting cigarette smoke-induced ferroptosis through the Nrf2-dependent signaling pathway [ 90 ]. Inflammatory macrophage accumulation has been recognized as a key factor involved in the progression of COPD, and mechanistic studies have shown that macrophages induce increased expression of ACSL4 in AT2 cells through arachidonate-5-lipoxygenase-mediated leukotriene B4 release, thereby rendering lung epithelial cells more susceptible to ferroptosis and injury [ 91 ]. These studies suggest that ferroptosis of airway epithelial cells may be an important mechanism underlying the progression of chronic inflammation in individuals with COPD and subsequent changes in airway fibrosis.…”
Section: Ferroptosis and Fibrosismentioning
confidence: 99%